2013
DOI: 10.15288/jsad.2013.74.223
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Use and Expectancies Predict Sexual Risk Taking Among Non-Problem Drinking Women

Abstract: ABSTRACT. Objective: Although alcohol consumption and sexual risk taking are associated, not everyone who drinks alcohol engages in risky sexual behavior. The purposes of the present study were to identify patterns of alcohol use behaviors and alcohol expectancies among women who are non-problem drinkers and to examine how these patterns are associated with indices of sexual risk. Method: Data from 758 non-problem drinking women who have sex with men and were not in committed relationships were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Within this high-risk population, results were consistent with national samples that point to female heterosexual orientation as a risk factor for prevalent HSV-2 infection. 29,30 They are also similar to prior studies linking alcohol consumption to risky sexual intentions, 31 risky sexual behaviors, [32][33][34][35] HSV-2 infection, 9,36 and other STDs, 33 an association especially important among HIVnegative individuals in this analysis (Table 2). Thus, in addition to screening for HSV-2 infection among all women experiencing housing instability, additional sexual risk and alcohol counseling may assist in tailoring services and interventions aimed at reducing HSV-2 in impoverished women.…”
Section: Discussionsupporting
confidence: 86%
“…Within this high-risk population, results were consistent with national samples that point to female heterosexual orientation as a risk factor for prevalent HSV-2 infection. 29,30 They are also similar to prior studies linking alcohol consumption to risky sexual intentions, 31 risky sexual behaviors, [32][33][34][35] HSV-2 infection, 9,36 and other STDs, 33 an association especially important among HIVnegative individuals in this analysis (Table 2). Thus, in addition to screening for HSV-2 infection among all women experiencing housing instability, additional sexual risk and alcohol counseling may assist in tailoring services and interventions aimed at reducing HSV-2 in impoverished women.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with numerous previous findings among the general adult population, our results revealed profiles that were composed of individuals who were at heightened alcohol risk and of co-occurring risk. For example, a recent study examining drinking patterns and sexual risk behaviors of 18- to 35-year-olds (of which 31% were college students and 7.9% were African American) found that frequent heavy drinkers had the greatest number of sexual partners and were the most likely to drink alcohol before having sex (Stappenbeck et al, 2013). Overall, results of the current latent class analysis suggest there is indeed significant variation in the risk behavior engagement of African American college students.…”
Section: Discussionmentioning
confidence: 99%
“…The SRAEs of African American women attending an STI clinic may result in high risk sex and also in unwanted/forced/coerced sex, and suggests the importance of developing integrated alcohol -sexual risk reduction interventions for high risk women (Sales et al, 2012; Stappenbeck et al, 2013). First, we recommend that such interventions increase self-awareness and self-monitoring by helping women identify their SRAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Women holding this SRAE are more likely to consume higher quantities of alcohol before sex and more likely to engage in risky sex after drinking (Crowe & George, 1989; Fromme, D'Amico, & Katz, 1999; Gilmore et al, 2013; Hendershot, Stoner, George, & Norris, 2007). Compared with women who have no or weak enhancement expectancies, women with strong enhancement SRAEs more often report intentions to have and/or history of: 1) sex with a casual partner (Abbey, Saenz, & Buck 2005; Cooper, 2002; George & Stoner, 2000; Parks, Hsieh, Collins, Levonyan-Radloff, & King, 2009); 2) sex with a new partner (Gilmore et al, 2013); 3) substance-impaired sex (Leigh, 1990; Weinhardt, Otto-Salaj, Brondino, Norberg, & Kalichman, 2002; White, Fleming, Catalano, & Bailery, 2009); 4) unprotected sex (Corbin & Fromme, 2002; Maisto, Carey, Carey, Gordon, & Schum, 2004); and 5) a greater number of sex partners [Hendershot et al, 2007; Stappenbeck, Norris, Kiekel, Morrison, George, Davis, Zawacki, Jacques-Tiura, & Abdallah, 2013; Weinhardt et al, 2002). Women with enhancement SRAEs are also more likely to report a history of sexual victimization (Marx, Nichols-Anderson, Messman-Moore, Miranda, & Porter, 2000; Testa & Dermen, 1999), which may occur as a consequence of engaging in risky sexually behaviors.…”
mentioning
confidence: 99%